Assessment of leadership development in the medical undergraduate curriculum: a UK consensus statement. Issue 4 (2nd July 2020) - Swanwick, Tim; McKimm, Judy
Abstract : With the increasing prominence of leadership within the medical undergraduate curriculum, assessment becomes a significant issue. In the absence of evidence to support specific strategies, tools or approaches, faculty from universities across the UK came together in October 2019 in a workshop convened by the Faculty of Medical Leadership and Management. The workshop aimed to develop a collective view on the assessment of leadership development in the medical undergraduate curriculum. This resulting consensus statement was generated around five prompts: why, what, how, when and who? In addition to the statement's key messages, several questions for further exploration were defined. See Box 1.